Digital experiences in creating digital services: case work for the rights of the child - López, Hugo-Andrés (Journal of the Belarusian State University. International Relations, 2020)
The digitalization process in the public sector has brought different benefits to states and their citizens, but it has also brought several challenges. In particular, digitalization processes require close collaboration with legal practitioners, managers and IT professionals, and failure to engage all participants means to come up with digital systems that do not comply with requirements, especially those related to laws. Currently, compliance is done in an after-the-fact fashion: a digital system is implemented, and legislators audit whether it abides legal constraints. The problem with this approach is the cost: in case of non-compliance, systems need to be re-implemented, and this will be most likely the case since laws are always changing. In this work we report experiences in compliant-by-design case work (CbDCW). In CbDCW, legal considerations are involved before the system is implemented, making compliance checking a task that can be automated. Moreover, the impact of a law change in implementation can be identified without needing to program a new solution. This paper reports our experiences in the application of CbDCW in the Danish public sector, as well as to propose a research agenda derived from these experiences. Overall we identified that there are key socio-technical differences between legal practitioners and process or IT developers, and that ensuring compliance requires these types of stakeholders to have a common understanding, which can be supported by hybrid-modeling techniques proper from business process management.
Keywords: Rights-by-design; Digitalization of the Public Sector; Regulatory Compliance; compliant-by-design case work